An accelerating&focusing structure with combined RF focusing for heavy ion accelerator - Dyachenko, A.F.; Zaytsev, B.V.; Tishkin, S.S.; Fedeneva, Ya.N.; Shulika, N.G.; Shulika, O.N. (Вопросы атомной науки и техники, 2014)
An accelerating&focusing channel of high-current linac for heavy ions with mass-to-charge ratio A/q ≤ 20 is presented. The channel is calculated to form and accelerate an ion beam from 6 keV/nucl. up to 1 MeV/nucl. An accelerator initial part based on a RFQ that provides acceleration from 6 to 100 keV/nucl. and a pre-stripping section with combined RF focusing for final acceleration up to 1 MeV/nucl. comprises the accelerating-focusing channel. It is proposed to use an IH structure for combined focusing. Numerical simulation of beam dynamics is performed. The channel allows ion beam acceleration at currents up to 10 mA.